Percepción sobre la violencia contra la mujer en el municipio de Vélez (Santander) (2016)
In accordance with the missional purpose of the National Police, this research was conducted with the aim of emphasizing the perception that people have against the scourge of violence against women in the municipality of Velez(Santander) in order to design an institutional strategy aimed at preventing psychosocial risk factors; regarding this matter four specific objectives were set: Identify the relationship between the sociodemographic characteristics of women 10 to 59 years old and the types of violence; characterize the relationship between types of violence and areas where violence occurs; typify the relationship between the sociodemographic characteristics of women between 10 and 59 years old also the areas where violence occurs and finally define strategies for awareness and prevention of the phenomenon of violence against women in the municipality of Vélez. This study covers in detail a more thorough look of the perception of women addressing violence that occurs against them in the town of Velez, comprising 4 types of violence such as physical, sexual, verbal and economic.